Update Breast Cancer 2022 Part 4 – Advanced-Stage Breast Cancer - Aktas, Bahriye; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Belleville, Erik; Untch, Michael; Thill, Marc; Tesch, Hans; Ditsch, Nina; Lux, Michael P.; Banys-Paluchowski, Maggie; Kolberg-Liedtke, Cornelia; Hartkopf, Andreas D.; Wöckel, Achim; Kolberg, Hans-Christian; Stickeler, Elmar; Harbeck, Nadia; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2022)
For the treatment of patients with advanced HER2-negative hormone receptor-positive breast cancer, several substances have been introduced into practice in recent years. In addition, other drugs are under development. A number of studies have been published over the past year which have shown either an advantage for progression-free survival or for overall survival. This review summarizes the latest results, which have been published at current congresses or in specialist journals, and classifies them in the clinical treatment context. In particular, the importance of therapy with CDK4/6 inhibitors – trastuzumab deruxtecan, sacituzumab govitecan and capivasertib – is discussed. For trastuzumab deruxtecan, an overall survival benefit in HER2-negative breast cancer with low HER2 expression (HER2-low expression) was reported in the Destiny-Breast-04 study. Similarly, there was an overall survival benefit in the FAKTION study with capivasertib. The lack of overall survival benefit for palbociclib in the first line of therapy raises the question of clinical classification.Für die Behandlung von Patientinnen mit fortgeschrittenem HER2-negativem, hormonrezeptorpositivem Mammakarzinom sind in den letzten Jahren einige Substanzen in die Praxis eingeführt worden. Zusätzlich sind weitere Medikamente in der Entwicklung. Im letzten Jahr sind einige Studien veröffentlicht worden, die entweder einen Vorteil für das progressions-freie Überleben oder aber auch für das Gesamtüberleben gezeigt haben. Diese Übersichtsarbeit fasst die neuesten Ergebnisse, welche auf aktuellen Kongressen oder in Fachzeitschriften veröffentlicht wurden, zusammen und ordnet sie in den klinischen Behandlungskontext ein. Insbesondere wird auf den Stellenwert einer Therapie mit CDK4/6 Inhibitoren, Trastuzumab-Deruxtecan, Sacituzumab-Govitecan und Capivasertib eingegangen. Für Trastuzumab-Deruxtecan wurde in der Destiny-Breast-04-Studie ein Gesamtüberlebensvorteil bei HER2-negativem Mammakarzinom mit einer niedrigen HER2-Expression (HER2-low expression) berichtet. Ebenso konnte ein Gesamtüberlebensvorteil in der FAKTION-Studie mit Capivasertib verzeichnet werden. Nach dem fehlenden Gesamtüberlebensvorteil für Palbociclib in der 1. Therapielinie stellt sich hier die Frage nach der klinischen Einordnung.
Keywords: advanced breast cancer; chemotherapy; endocrine therapy; antibody drug conjugates